Effect of artificial defoliation on the emergence of foliar buds of Mimosa pigra - A. Nur Zhafarina; M. Asyraf; Z. Latifah (Syiah Kuala University, 2012)
This study was specified in documenting Mimosa reaction in the state of defoliation on the plants. As defoliation was believed to cause plants experiencing both positive and/or negative effects on its growth performance, thus among the aim of this study is to monitor the emergence of foliar buds in respond with vary level of defoliation intensities. The seedlings were grown singly in polybags up to four leaf stage as. Grown seedlings were randomly subjected under four different defoliation intensities: control (un-defoliated), 25%, 50%, and 100% in which 10 replicates of seedling for each treatment. Experiment was ceased at the 6th month after establishment of plants grew. Results shown that, the effect of defoliation on the production of foliar buds was significantly difference between the treatments (P 0.05). As compared with 25%, 50% and 100% defoliation, un-defoliated plants showed the highest amount of foliar buds production which is 14 buds. While, there were no differences amount of foliar buds production between 25% and 50% defoliation with 5 foliar buds per plants. Emergence of foliar buds was reportedly lowest in 100% defoliation plant when there were no sign of buds emergence. Results concluded that, the subjected plants of control, 25% and 50% leaves defoliation treatments, were able to performed tolerance effect relative to the induced stressor. Apart from that, experiment revealed that the 100% defoliation has probability of detrimental effect on growth and reproduction of Mimosa seedling as it hindrance the germination of foliar buds.